Validación del cuestionario de calidad de vida en hipertensión arterial (CHAL) para su uso en España. Relación entre variables clínicas y calidad de vida - Dalfó Baqué, A. (Aten Primaria, 2000)
OBJECTIVE: To evaluate the measurement properties of the Hypertension Quality of Life (HQALY) questionnaire, under normal clinical practice conditions, and the relationship between quality of life and clinical variables in patients with hypertension. DESIGN: Observational, prospective and multi-centred study. SETTING: 92 primary care centres in Spain. PARTICIPANTS: 269 patients, of both sexes and over 17, with hypertension, stratified by age (18-44, 45-64 and over 64), sex and organic complaint. 106 individuals over 17 with normal tension were chosen at random. INTERVENTIONS: Intensification of treatment in hypertense patients. MEASUREMENTS: Administration of the HQALY and the EuroQol-5D at every attendance (patients, basal and at a month; controls, basal). In addition, at the basal attendance social-demographic and clinical features were recorded, and at the attendance at a month the clinical features and changes in health status. MAIN RESULTS: Mean time of administration was 28 (23) minutes. Validity: factor analysis showed two dimensions, state of mind and somatic manifestations, which correlated most closely with the dimensions of anxiety/depression (0.64) and pain/discomfort (0.55) on the EQ-5D, respectively. HQALY scores were higher (worse quality of life) in patients than in controls without hypertension (p < 0.01). Reliability: intraclass correlation coefficient was 0.88 in state of mind and 0.76 in somatic manifestations. Cronbach’s alpha was 0.96 and 0.89, respectively. Sensitivity: the «size of the effect» at a month from starting treatment for hypertension was 0.40. Hypertension for over 10 years, more organs affected, gravity and morbid obesity were associated with worse quality of life, especially in the state-of-mind dimension. Cardiac frequency correlated closer with state of mind than somatic manifestations. CONCLUSIONS: The HQALY is the first specific hypertension questionnaire developed in Spain which has been shown valid, reliable and sensitive to changes. However, the number of items on it must be reduced for routine use in clinical practice.